2021
DOI: 10.3390/cells10071673
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Seed Transmission of Tomato Yellow Leaf Curl Sardinia Virus in Tomato

Abstract: Seed transmission is an important factor in the epidemiology of plant pathogens. Geminiviruses are serious pests spread in tropical and subtropical regions. They are transmitted by hemipteran insects, but a few cases of transmission through seeds were recently reported. Here, we investigated the tomato seed transmissibility of the begomovirus tomato yellow leaf curl Sardinia virus (TYLCSV), one of the agents inducing the tomato yellow leaf curl disease, heavily affecting tomato crops in the Mediterranean area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…While the significant reduction in TYLCV DNA load after surface disinfection of tomato seeds suggests that the virus can be the contaminant of the seed coat, transmission assays carried out with seven tomato genotypes and more than 3,000 tomato plants revealed no evidence of seed transmission from "surface-disinfected" or untreated seed for two Mediterranean isolates of TYLCV-IL (Pérez-Padilla et al 2020). Supporting this finding, Tabein et al (2021) also found no evidence for the tomato seed transmissibility of tomato yellow leaf curl Sardinia virus (TYLCSV), one of the agents inducing the TYLCD. Therefore, TYLCV-IL is seed-borne but is not seed transmitted in tomato or N. benthamiana, suggesting that transmission through seed is not a general property of TYLCV.…”
Section: Provincial-level Administrative Regionmentioning
confidence: 78%
“…While the significant reduction in TYLCV DNA load after surface disinfection of tomato seeds suggests that the virus can be the contaminant of the seed coat, transmission assays carried out with seven tomato genotypes and more than 3,000 tomato plants revealed no evidence of seed transmission from "surface-disinfected" or untreated seed for two Mediterranean isolates of TYLCV-IL (Pérez-Padilla et al 2020). Supporting this finding, Tabein et al (2021) also found no evidence for the tomato seed transmissibility of tomato yellow leaf curl Sardinia virus (TYLCSV), one of the agents inducing the TYLCD. Therefore, TYLCV-IL is seed-borne but is not seed transmitted in tomato or N. benthamiana, suggesting that transmission through seed is not a general property of TYLCV.…”
Section: Provincial-level Administrative Regionmentioning
confidence: 78%
“…In contrast, other works have observed no evidence for TYLCV seed transmissibility in Nicotiana benthamiana [38]. Likewise, recent studies on tomato have reported the absence of TYLCV and tomato yellow leaf curl Sardinia virus (TYLCSV) transmission through infected seeds in tests performed at different locations [39,40]. Finally, the seed transmission of SPLCV was not detected after the recent large-scale screening of sweet potato plants [33][34][35][36]41].…”
Section: Introductionmentioning
confidence: 92%
“…k. Tomato yellow leaf curl Sardinia virus (TYLCSV) is an important monopartite begomovirus responsible for worldwide spread of TYLCD in association with TYLCV and other TYLCV-like viruses ( Moriones and Navas-Castillo, 2000 ). The seed transmission nature of TYLCSV was studied in highly susceptible tomato cultivar Money Maker through agro-inoculation with 1.8mer TYLCSV construct ( Tabein et al., 2021 ). The agro-inoculated plants showed the typical symptoms of TYLCSV, viz ., severe leaf curling, cupping, and yellowing on newly emerged leaves.…”
Section: Emerging Evidence For Seed-borne Nature Of Begomov...mentioning
confidence: 99%